Análise numérica de estruturas de no de pórtico em concreto armado considerando dano e plasticidade - Fritzen, Leonardo Luiz (2024)
Joints are volumes located in the region of competition between beams and columns. They participate in the distribution of vertical and horizontal loads, being subject to high shear forces and high bending moments. Its sizing is complex and depends on several variables. In this way, a study was carried out on the application of the concrete damaged plasticity model in simulations of external joints of reinforced concrete, subjected to opening moment (positive moment) in a monotonic way in the ABAQUS program that uses the finite element method. The main advantage of the concrete damaged plasticity model is the ability to capture the nonlinear behavior and propagation of cracks in concrete. The damage variables for traction and compression were defined using the Alfarah et al. (2017) methodology and the modeling was representative of the RV9, RV10 and RV11 specimens from the Johansson (2001) experimental study. The simulations were carried out in order to define the influence of the viscosity parameter, the dilatation angle and the size of the finite element mesh on numerical convergence and results relating to resistance and cracking pattern. Viscoplastic regularization proved to be of great importance for the convergence of numerical simulations and the value of viscosity parameter that provided the most appropriate results was 0.00005. As for the dilatation angle, there was a subtle increase in resistance the higher the value of this parameter. The finite element mesh that proved to be most suitable was 1 cm, as it provided a similar damage pattern to the cracks in the experimental tests in a viable computational processing time. After defining the most appropriate parameters for the numerical simulations, the results varied on average by 29% in relation to the maximum resistance of the experimental tests, which are representative, but were very precise in relation to the displacement at which the maximum force occurs.